Characteristics of patients with chronic heart failure with mildly reduced ejection fraction: clinical and demographic aspect - M. T. Duishenalieva; A. G. Polupanov; F. T. Rysmatova; E. Zh. Myrzabekova; N. E. Esenbekova; N. Ch. Cholponbekova; E. Sh. Altymyshova; A. T. Arykova; N. B. Cheskidova; E. D. Djyshambaev (Acta Biomedica Scientifica)
Introduction. A new class of chronic heart failure (CHF) has been identified recently – heart failure with mildly reduced left ventricular ejection fraction (HFmrEF). The determinants and outcomes of this phenotype are still being clarified.The aim. To study the clinical and demographic characteristics of patients with HFmrEF. Materials and methods. A retrospective analysis of 1141 medical records of patients with CHF who were hospitalized at the National Center of cardiology and Internal medicine named after M. Mirrakhimov were conducted. Patients were categorized as follows: 39.4 %, 23.3 % and 37.3 % of patients with CHF with low, mildly reduced and preserved left ventricular ejection fraction, respectively. Demographic indicators, causes and severity of CHF, risk factors, and comorbidities were assessed in all patients.Results. Patients with HFmrEF were comparable to those with HFrEF in terms of demographic characteristics and etiology. Among HFmrEF patients, men predominated (62 %), with an average age of 63,9 years. The most common causes of HFmrEF were coronary heart disease (CHD) (81,6 %), hypertension (7,3 %) and their combination (22,1 %). The incidence of obesity and atrial fibrillation in the HFmrEF group was 35,3 % and 28,6 %, respectively, and did not differ significantly from that in patients with HFrEF. A significantly lower prevalence of chronic kidney disease and chronic obstructive pulmonary disease was observed in the HFmrEF and HFpEF groups compared to the HFrEF group. Type 2 diabetes mellitus was present in approximately one in five patients, regardless of the CHF phenotype. Patients with functional class III (NYHA) predominated among those with HFmrEF (54,5 %) and HFrEF (56,3 %).Conclusion. Patients with HFmrEF were comparable to those with HFrEF in most clinical and demographic characteristics and in the severity of CHF.